Carbene-catalyzed enantioselective carbon-heteroatom bond (C-N, C-P, C-S) construction - Rakesh, Maiti (Nanyang Technological University, 2021)
N-Heterocyclic carbene (NHC) has emerged as one of the crucial synthetic tools for asymmetric transformations of readily available materials into complex moieties. Particularly, a great deal of success has been achieved on the front of enantioselective carbon-carbon bond formation. However, in sharp contrast, NHC-mediated asymmetric carbon-heteroatom bond (C-X) construction was seldomly explored. In this thesis, three novel NHC-catalyzed strategies have been developed to access C-N, C-P, and C-S bonds asymmetrically. Firstly, utilization of the NHC-bound unsaturated acyl azolium intermediate has been demonstrated to access dihydropyrimidinone scaffold (C-N bond formation) and carbon-centered chiral tertiary phosphine (C-P bond formation). In the last part, rarely explored NHC-bound alkynyl acyl azolium intermediate has been discussed and applied to obtain atroposelective axially chiral sulfone-bearing styrene derivatives (C-S bond formation).